Preparation of superhydrophobic membranes and their application in membrane distillation - Tian, M.; Li, X.; Yin, Y.; He, T.; Liu, Jian (2015)
©, 2015, Chinese Academy of Sciences. All right reserved. Superhydrophobic surfaces are characterized by their high water repellency and self-cleaning properties, which is potentially applicable in areas where anti-wetting and anti-fouling properties are highly desired. Membrane distillation (MD) is driven by the vapor pressure gradient across a porous hydrophobic membrane, and is versatile in desalination and water reclamation processes. However, membrane wetting and fouling are two major issues in the application of MD. Based on the state-of-art development of MD, this mini-review provides an overview on the preparation of superhydrophobic membranes and their application in MD. The merits of application of superhydrophobic membranes are illustrated, in addition to the shortcomings of superhydrophobic surfaces. This review is critical in pointing out new research directions and schemes for the development of the MD membrane.